Public capital contribution to economic growth in Ecuador: empirical evidence - Díaz Kovalenko, Igor Ernesto (2026)
This article examines the contribution of public capital to Ecuador’s economic growth over the period 1960-2019 by employing a general equilibrium model with an extended Cobb-Douglas production function that incorporates public capital as an additional input. Based on the calibration of structural parameters using data from PWT11, the Central Bank of Ecuador, the IMF, and the Investment and Capital Stock Dataset (2019), total factor productivity (TFP) is estimated and a growth accounting exercise is carried out following Solow’s (1956) methodology and the empirical approach proposed by Torres-Chacón (2009). The results show that public capital has an output elasticity of 0.10 and contributes, on average, 0.40 percentage points to annual GDP growth, representing approximately 13% of total economic growth during the period studied. Private capital remains the main driver of growth, whereas TFP displays considerable volatility and prolonged episodes of negative contribution, particularly between 1973 and 1999. The findings indicate that public capital complements—rather than substitutes—private capital, and that its effectiveness depends on investment efficiency, macroeconomic stability, and infrastructure quality. The results are consistent with international evidence, particularly the Spanish case, and provide relevant insights for designing policies aimed at promoting sustained growth and improving productivity.